Hubungan Kebiasaan Merokok Remaja Dengan Gangguan Pola Tidur - Vaora, Muthia -; Sabrian, Febriana -; Dewi, Yulia Irvani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The purpose of this research was to determine the relationship between teen smoking behavior and insomnia. The method of this research was descriptive with cross sectional method. Research was at SMAN 9 Pekanbaru involving 81 respondents. The sampling technique used was quota sampling. The measuring tool used were questionnaires that have been modified and tested validity and reability. This research used chi-square test for bivariate analysis. The result showed that 34 respondents (42%) are light smokers and 69 respondents (85,2%) experience insomnia. There are sidnificant re;ationship between teen smokers behavior and insomnia (p value < 0,05). It is recommended for the school to conduct health promotion activities regarding the dangerous effect of smokers. Keywords: adult, cigarettes, insomnia Reference: 23(2002 – 2011)